The Effect Of Return On Asset, Company Age, And Sales Growth On Tax Avoidance With Company Size As A Moderating Variable : Pengaruh Return On Asset, Umur Perusahaan, Dan Pertumbuhan Penjualan Terhadap Tax Avoidance Dengan Ukuran Perusahaan Sebagai Variabel Moderating - Laili Faradia; Herman Ernandi (Academia Open, 2021)
This study aims to determine the effect of Return On Assets,Company Age and Sales Growth on Tax Avoidance with Company Size as Moderating Variables.This study used quantitative research methods.In this case the object of research is a manufacturing company in the consumer goods industry sector which is listed on the Indonesia Stock Exchange during 2017-2019 using the purposive sampling method.Samples collected in this study comes from secondary data obtained through the documentation technique as much as 25 companies with total sample as many as 75 sample companies.Analysis technique data used that includes the outer model, inner model and path analysis with Smart PLS 3.2.8 for windows program.The results of this study are that Return On Assets and Sales Growth has no significant effect on the implementation of Tax Avoidance which is moderated by Companey Size and Company Age has a positive and significant effect on the implementation of Tax Avoidance and is moderated by Companey Size Keywords–Return On Asset;Firm Age;Sales Growth;Firm Size;Tax Avoidance Abstrak.Penelitian ini bertujuan untuk mengetahui pengaruh Return On Asset, Umur Perusahaan, dan Pertumbuhan Penjualan Terhadap Tax Avoidance dengan Ukuran Perusahaan Sebagai Variabel Moderating.Pada penelitian ini menggunakan metode penelitian kuantitatif.Dalam hal ini yang menjadi obyek penelitian adalah perusahaan manufaktur sektor industry barang konsumsi yang terdaftar di Bursa Efek Indonesia selama tahun 2017–2019 dengan menggunakan metode purposive sampling.Sampel yang digunakan dalam peneltian ini sebanyak 25 perusahaan dengan jumlah keseluruhan 75 sampel.Teknik analisis menggunakan data yang meliputi outer model, inner model dan analisis jalur dengan program Smart PLS 3.2.8 for windows.Hasil penelitian ini adalah Return On Assets dan Pertumbuhan Penjualan tidak berpengaruh secara signifikan terhadap penerapan Tax Avoidance yang dimoderasi oleh Ukuran Perusahaan dan Umur Perusahaan memiliki pengaruh positif dan signifikan terhadap penerapan Tax Avoidance dan dimoderasi oleh Ukuran Perusahaan. Kata kunci–Return On Asset;Ukuran Perusahaan;Pertumbuhan Penjualan;Ukuran Perusahaan;Tax Avoidance